Low-cost, on-farm intervention to reduce spores in bulk tank raw milk benefits producers, processors, and consumers - Rachel L. Evanowski; Sarah I. Murphy; Martin Wiedmann; Nicole H. Martin (Journal of Dairy Science, 2023)
ABSTRACT: Bacterial spores, which are found in raw milk, can survive harsh processing conditions encountered in dairy manufacturing, including pasteurization and drying. Low-spore raw milk is desirable for dairy industry stakeholders, especially those who want to extend the shelf life of their product, expand their distribution channels, or reduce product spoilage. A recent previous study showed that an on-farm intervention that included washing towels with chlorine bleach and drying them completely, as well as training milking parlor employees to focus on teat end cleaning, significantly reduced spore levels in bulk tank raw milk. As a follow up to that previous study, here we calculate the costs associated with that previously described intervention as ranging from $9.49 to $13.35 per cow per year, depending on farm size. A Monte Carlo model was used to predict the shelf life of high temperature, short time fluid milk processed from raw milk before and after this low-cost intervention was applied, based on experimental data collected in a previous study. The model predicted that 18.24% of half-gallon containers of fluid milk processed from raw milk receiving no spore intervention would exceed the pasteurized milk ordinance limit of 20,000 cfu/mL by 17 d after pasteurization, while only 16.99% of containers processed from raw milk receiving the spore intervention would reach this level 17 d after pasteurization (a reduction of 1.25 percentage points and a 6.85% reduction). Finally, a survey of consumer milk use was conducted to determine how many consumers regularly consume fluid milk near or past the date printed on the package (i.e., code date), which revealed that over 50% of fluid milk consumers surveyed continue to consume fluid milk after this date, indicating that a considerable proportion of consumers are exposed to fluid milk that is likely to have high levels spore-forming bacterial growth and possibly associated quality defects (e.g., flavor or odor defects). This further highlights the importance of reducing spore levels in raw milk to extend pasteurized fluid milk shelf life and thereby reducing the risk of adverse consumer experiences. Processors who are interested in extending fluid milk shelf life by controlling the levels of spores in the raw milk supply should consider incentivizing low-spore raw milk through premium payments to producers.